ULU AMBEK: SEBUAH PERTARUHAN NILAI - Dilmai Putra; Koes Yuliadi; Wilma Sriwulan (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2016)
ABSTRACT Ulu ambek is the battle among nagari (=villages) and among their customary leaders through their fighters namely pandeka ulu ambek. The battle is the fight of values which stakes the greatness, honor, and prestige of a nagari and all of its equipments. The battle is done in order to gain recognition and existence from other nagari. Ulu ambek is conceptualized and created as a battle which honors sportsmanship, ethics, and aesthetics. Sportsmanship can be seen from its rules and the rule keepers; ethics can be seen from the way to do it; and aesthetics can be seen from the movement. In Minangkabau society, the terms balahie babatin means that there are things that can be seen physically and the others that can only be felt mentally. In physical appearance, ulu ambek is seen as an attractive movement that’s equal to suntiang, a traditional head ornament of Minangkabaunese’s bride. In spiritual way, ulu ambek is a battle using spiritual and supernatural power. Through the spiritual and supernatural power, ulu ambek is presented in the movements of attacking and repelling opponent’s strike without any physical contact.                                                                                                                      Keywords: Ulu ambek, battle, value, ethics, sportsmanship, nagari